2017
DOI: 10.1186/s12876-017-0631-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimal timing of cholecystectomy after percutaneous gallbladder drainage for severe cholecystitis

Abstract: BackgroundThe Tokyo guideline for acute cholecystitis recommended percutaneous transhepatic gallbladder drainage followed by cholecystectomy for severe acute cholecystitis, but the optimal timing for the subsequent cholecystectomy remains controversial.MethodsSixty-seven patients who underwent either laparoscopic or open cholecystectomy after percutaneous transhepatic gallbladder drainage for severe acute cholecystitis were enrolled and divided into difficult cholecystectomy (group A) and non-difficult cholecy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 28 publications
(28 reference statements)
2
32
0
Order By: Relevance
“…In the study by Altieri et al[ 23 ] of 2998 patients who underwent cholecystectomy following PC, 47 (1.6%) patients experienced common bile duct injury. Some studies suggest that risks may be increased further when LC is performed at an early stage after PHGD in high-risk patients[ 24 ]. El-Gendi et al[ 13 ] and Ke and Wu[ 25 ] reported good outcomes when LC was performed after waiting 4-6 wk after PHGD.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Altieri et al[ 23 ] of 2998 patients who underwent cholecystectomy following PC, 47 (1.6%) patients experienced common bile duct injury. Some studies suggest that risks may be increased further when LC is performed at an early stage after PHGD in high-risk patients[ 24 ]. El-Gendi et al[ 13 ] and Ke and Wu[ 25 ] reported good outcomes when LC was performed after waiting 4-6 wk after PHGD.…”
Section: Discussionmentioning
confidence: 99%
“…Because most studies (15)(16)(17) figure out the short interval increases intraoperative difficulty, we require all patients to undergo cholecystectomy 3 months after drainage, so that edema and inflammation around the gallbladder subsided completely.…”
Section: Interventionsmentioning
confidence: 99%
“…The patients who need surgery intervention are suggested to be evaluated using the Charlson Comorbidity Index (CCI) [18][19][20] or the American Society of Anesthesiologists physical status classi cation (ASA-PS) [21,22]; PT-GBD is useful for managing high surgical risk patients compared with conservative treatment [9,23,24]. CCY can decrease further recurrent biliary events (RBEs) [25,26], while the surgery timing after patients with acute cholecystitis have undergone PT-GBD is still in debate [27][28][29][30][31][32]. Currently, there is no strong evidence to suggest who has survival bene ts from subsequent CCY after initial PT-GBD, but a similar concept in choledocholithiasis demonstrated that a prophylactic CCY in acute cholangitis patients who underwent sphincterotomy showed survival bene t compared to the wait-and-see approach [33].…”
Section: Introductionmentioning
confidence: 99%